Effects of N‐acetylcysteine on oxidative stress biomarkers, depression, and anxiety symptoms in patients with multiple sclerosis - Golsa Khalatbari Mohseni; Seyed Ahmad Hosseini; Nastaran Majdinasab; Bahman Cheraghian (Wiley, 2023)
Abstract Aim N‐acetylcysteine (NAC), a thiol‐containing antioxidant and glutathione (GSH) precursor, attenuates oxidative stress, and possibly improves psychiatric disorders. This study aimed to evaluate the effects of oral NAC on oxidative stress, depression, and anxiety symptoms in patients with multiple sclerosis (MS). Methods This clinical trial was conducted on 42 MS patients randomly assigned to intervention (n = 21) and control (n = 21) groups. The intervention group received 600 mg of NAC twice daily for 8 weeks, and the control group received a placebo with the same prescription form. An analysis of serum malondialdehyde (MDA), serum nitric oxide (NO), and erythrocyte GSH was carried out on both groups, along with a complete blood count. The Hospital Anxiety and Depression Scale (HADS) was used to assess symptoms of depression (HADS‐D) and anxiety (HADS‐A). Results Compared to the control group, NAC consumption significantly decreased serum MDA concentrations (−0.33 [−5.85-2.50] vs. 2.75 [−0.25-5.22] μmol/L; p = 0.03) and HADS‐A scores (−1.6 ± 2.67 vs. 0.33 ± 2.83; p = 0.02). No significant changes were observed in serum NO concentrations, erythrocyte GSH levels, and HADS‐D scores (p > 0.05). Conclusions Based on the findings of the present study, NAC supplementation for 8 weeks decreased lipid peroxidation and improved anxiety symptoms in MS patients. The aforementioned results suggest that adjunctive therapy with NAC can be considered an effective strategy for MS management. Further randomized controlled studies are warranted.